Effect of Picotamide on Platelet Aggregation and on Thromboxane A2 Production In Vivo - Minuz, P; Lechi, C; Arosio, E; Guzzo, P; Zannoni, M; Lauciello, C; Lechi, A (Thrombosis and Haemostasis, 1991)
Effects of picotamide (900 mg in 3 oral administrations for 7 days) on ex vivo and in vivo platelet T×A2 production and on platelet aggregation wpre evaluated in 8 patients with peripheral arteriopathy and in 8 normal subjects. Picotamide significantly reduced ADP-induced platelet aggregation, but had no effect on that induced by arachidonic acid or the thromboxane analogue U46619. Though ex vivo platelet T×A2 production (T×B2 concentration after arachidonic-acid-induced aggregation) was reduced from 946 ± 141 (mean ± SD) to 285 ± 91 ng/ml in controls and from 1515 ± 673 to 732 ± 420 ng/ml in patients with arteriopathy, there was no effect on urinary excretion of 2,3-dinor-T×B2 (in vivo indicator of platelet T×A2 production), or on in vivo PGI2 production (urinary excretion of 6-keto-PGF1α and 2,3-dinor-6-keto-PGF1α). In the same subjects, single-dose aspirin reduced ex vivo T×B2 production by at least 98% and 2,3-dinor-T×B2 excretion from 116.7 ± 61.4 to 32.6 ± 17.0 nglg creatinine in control subjects, and from 156.3 ± 66.1 to 59.1 ± 19.2 ng/g creatinine in patients with peripheral arteriopathy. Our data suggest that inhibition of platelet T×A2 production in vivo may not be picotamide’s main mechanism of action.